The Lorenz Energy Cycle of the Global Atmosphere during the past 35 Years (1979-2013) - Pan, Yefeng 1989- (2015)
The Lorenz energy cycle (Lorenz 1955) describes how the solar heating generates potential energy that can be converted into kinetic energy to drive Earth’s atmospheric system. Therefore, the studies of the Lorenz energy cycle can help us understand the atmospheric system from a unique energy perspective. Based on two best global meteorological datasets, we systematically study the Lorenz energy cycle of the global atmosphere during the modern satellite era (1979-2013). Our analyses provide the most reliable characteristics of the Lorenz energy cycle of the global atmosphere. The mean state of the 35-year Lorenz energy cycle generates the best global picture of the Lorenz energy cycle. Our analyses also reveal important temporal characteristics of the Lorenz energy cycle of the global atmosphere. Significant positive trends are shown in both the eddy available potential energy (P_E) and the eddy kinetic energy (K_E) especially in the Southern Hemisphere, which are mainly due to the increasing storm activities over the Southern Ocean storm track areas. At the same time, a negative trend is seen in the mean available potential energy (P_M) especially around the North Pole near the surface, which is probably related to the inhomogeneous global warming. As a result, the total mechanical energy does not show any significant trend during the past 35 years, which suggests that the climate system remains close to a dynamical balance. Our analyses also suggest positive trends in all conversion rates and in the dissipation of kinetic energy, which implies that the efficiency of the global atmosphere as a heat engine increased during the modern satellite era. The statistical characteristics of the Lorenz energy cycle revealed in our analyses will provide a powerful tool to validate and develop the atmospheric and climate models. The temporal characteristic of the Lorenz energy cycle will also benefit the monitoring and predicting of climate change, for the atmospheric energetics are an important component of climate system ...